Fishing Tourism of Conflict Area in South Kalimantan - Rochgiyanti, Rochgiyanti; Arisanty, Deasy; Hastuti, Karunia Puji (Technium Social Sciences Journal, 2023)
Wetland areas are rich with inland fisheries potential. However, the entry of oil palm plantations has threatened the existence of wetland ecosystems. Community rejection of the entry of oil palm plantations has created conflict between the two parties. Even though it is in a conflict area, the fishery potential has encouraged the development of fishing tourism which invites local tourists. The development of fishing tourism in wetlands not on contributes to the rotation of the rural economy and the study of social sciences. This study aims to determine the driving factors for the development of fishing tourism and their contribution to the community's economy. The research method used is qualitative research locations are villages that develop fishing tourism in South Kalimantan Province. Interviews were conducted with fish well owners, anglers, formal and non-formal figures, and community members who have businesses around fishing locations. The informants were 64 people. Observations were made of fishing objects. Document studies and audio-visual recordings were carried out regarding the activities of anglers. Data analysis uses an emic perspective, so an overview of fishing tourism from the point of view of the research subject. The results of the study show that the driving factors for the development of fishing tourism are wetland ecosystems as freshwater fish habitats and open road access, both opened by oil palm plantation companies and local governments. The development of this new type of business has contributed to the owners of fish wells and the informal business sector around fishing grounds. The conclusion is that fishing tourism can still be developed even though it is in a conflict area. The implication is the occurrence of economic cycles in rural areas and the sustainability of natural resources.